The true Herod - Vermès, Géza (Bloomsbury, 2014)
Who was Herod the Great? How did he come to govern one of the most politically tumultuous regions in the world? Was he the heartless baby-killer of Matthew's Gospel, or does this popular tale do Herod a great disservice? Geza Vermes, whose work on the Historical Jesus and the Dead Sea Scrolls has made him one of the most recognisable names in Biblical and Jewish studies, provides a new portrait of Herod. Vermes examines Herod's legacy as a political leader, and a potentate, a man of culture, and an all-round smooth operator. Vermes opens up the fascinating character of Herod, from his sizable and fragile ego to his devastation at the execution of his beloved wife, an execution that Herod ordered himself. Beginning with the key historical sources (notably Josephus) Vermes moves on to consider Herod's greatest legacy and testament - his extensive building works, which include the Temple in Jerusalem, Masada and Herodium. Colour images, combined with Vermes' lively prose make this new picture of Herod an enticing and informative guide to one of ancient history's most misunderstood figures